2021
DOI: 10.3390/life11040289
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: Potential Targets for Developing Stress-Tolerant Crops

Abstract: Crop yield is challenged every year worldwide by changing climatic conditions. The forecasted climatic scenario urgently demands stress-tolerant crop varieties to feed the ever-increasing global population. Molecular breeding and genetic engineering approaches have been frequently exploited for developing crops with desired agronomic traits. Recently, microRNAs (miRNAs) have emerged as powerful molecules, which potentially serve as expression markers during stress conditions. The miRNAs are small non-coding en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 198 publications
(265 reference statements)
2
6
0
Order By: Relevance
“…in which it has been reported that, in general, miRNAs reactive to stress target predominantly TFs (Samad et al, 2017). This reinforces the emerging notion that the role played by miRNAs during the stress response is evolutionary conserved in plants (Rubio-Somoza and Weigel, 2011;Megraw et al, 2016;Sanz-Carbonell et al, 2020) and emphasizes the potential of miRNAs as targets for improving stress tolerance in crops (Tang and Chu, 2017;Chaudhary et al, 2021). The totality of these stress-responsive miRNA families was coincident with the previously described as reactive in single biotic and abiotic stress conditions in melon (Sanz-Carbonell et al, 2019.…”
Section: Discussionsupporting
confidence: 82%
“…in which it has been reported that, in general, miRNAs reactive to stress target predominantly TFs (Samad et al, 2017). This reinforces the emerging notion that the role played by miRNAs during the stress response is evolutionary conserved in plants (Rubio-Somoza and Weigel, 2011;Megraw et al, 2016;Sanz-Carbonell et al, 2020) and emphasizes the potential of miRNAs as targets for improving stress tolerance in crops (Tang and Chu, 2017;Chaudhary et al, 2021). The totality of these stress-responsive miRNA families was coincident with the previously described as reactive in single biotic and abiotic stress conditions in melon (Sanz-Carbonell et al, 2019.…”
Section: Discussionsupporting
confidence: 82%
“…The present study and our previous one (Salgado et al, 2021) used plants with the same genetic background (clones from the same plant), the same age (young oil palm plants), almost similar duration of stress (12 and 14 days, respectively for salinity and drought stress), same omics platform (transcriptome of mRNAs and smallRNAs), and the same group of analytical tools. All these commonalities between these two studies allowed us analyze the similarities and dissimilarities regarding expression analysis of miRNAs and their putative target genes, what it a valuable set of information to help us in the search for genes that can be used to promote future attempts to horizontally transfer tolerance at once to both stresses; not only to oil palm, but also other plant species (Patel et al, 2019;Chaudhary et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, both mechanisms require an almost perfect base pairing between miRNAs and their mRNA targets [ 12 , 13 ]. miRNAs are known to be major regulators of developmental processes and of biotic and abiotic stress responses in plants, as summarized in recent articles [ 14 , 15 , 16 ]. Among them, plant miRNAs identified in temperature stress response have been the subject of dedicated reviews [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%